2003
DOI: 10.1016/s1063-4584(02)00354-0
|View full text |Cite
|
Sign up to set email alerts
|

FGF signaling antagonizes cytokine-mediated repression of Sox9 in SW1353 chondrosarcoma cells

Abstract: SW1353 cells represent a useful human cell model as they conserve many Sox9 signaling pathways previously demonstrated in mouse chondrocytes. We identify FGF-9 as a particularly potent Sox9 agonist. The antagonism between FGFs and cytokines on Sox9 expression and Col2 enhancer activity suggests that Sox9 integrates the opposing activities of FGFs and cytokines. We also find that SW1353 cells respond to very low doses of IL-1 with Col2 enhancer activation, while increasing doses lead to repression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…TGF-␤ signaling is a major influence in promoting HSC activation and subsequent COL1 expression; fibroblast growth factor 2 augments ECM deposition (29,45,46). We showed that TGF-␤ increased SOX9 expression in two HSC models, similar to observations in developing chondrocytes (47); previously, fibroblast growth factor 2 increased both SOX9 transcripts and protein in a chondrosarcoma cell line (48). Moreover, both TGF-␤ and fibroblast growth factor 2 promote epithelial-tomesenchymal transition (EMT), whereby quiescent epithelial cells morph into myofibroblast-like cells characterized by ␣-SMA.…”
Section: Discussionsupporting
confidence: 80%
“…TGF-␤ signaling is a major influence in promoting HSC activation and subsequent COL1 expression; fibroblast growth factor 2 augments ECM deposition (29,45,46). We showed that TGF-␤ increased SOX9 expression in two HSC models, similar to observations in developing chondrocytes (47); previously, fibroblast growth factor 2 increased both SOX9 transcripts and protein in a chondrosarcoma cell line (48). Moreover, both TGF-␤ and fibroblast growth factor 2 promote epithelial-tomesenchymal transition (EMT), whereby quiescent epithelial cells morph into myofibroblast-like cells characterized by ␣-SMA.…”
Section: Discussionsupporting
confidence: 80%
“…As cellular models we used HEK293 human embryonic kidney cells (56) and SW1353 human humeral bone chondroblast cells (45). SW1353 cells do not express paralogy group 13 and the majority of other Hox genes (V. Salsi and V. Zappavigna, unpublished results), and conserve many of the signaling pathways of primary chondrocytes (53). Conversely, HEK293 cells express HOXD13 endogenously (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SW1353 cells as well as other chondrocytic tumor cells, including OUMS-27 and HCS-2/8, have been used in many studies as a reliable substitute for primary human chondrocytes. They represent a useful tool with which to investigate the expression of cartilage matrix proteins (17,18), proinflammatory cytokines (19,20), MMP (19,(21)(22)(23)(24), TIMP (18) and chondrocytic transcription factor expression (20,25,26). In a recent publication, comparison of SW1353 cells to primary chondrocytes was described with respect to their gene expression profile and IL-1 responsiveness (27).…”
Section: Discussionmentioning
confidence: 99%